Peran Media Sosial dalam Pembentukan Tren Restorasi Motor Mio di Bali: Studi pada Komunitas Pecinta Otomotif - Nyoman Sri Manik Parasari; Putu Nico Pratama Kusuma Wardana; I Putu Dharmawan Pradhana; Ni Putu Yunita Anggreswari (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyse the role of social media in shaping trends in the restoration of Mio motorbikes in Bali. The study employs a qualitative approach using descriptive methods. Data were collected through in-depth interviews, observation and documentation involving seven informants, comprising spare parts distributors, members of the Mio motorbike enthusiasts’ community, consumers and social media observers. Data analysis was carried out using the Miles and Huberman interactive model, which encompasses data reduction, data presentation and drawing conclusions. The results of the study indicate that social media serves as a means of disseminating information, forming communities, strengthening social networks, and providing a platform for expression among Mio motorbike restoration enthusiasts. Platforms such as Instagram, Facebook and YouTube make it easier for users to access restoration references, source spare parts, build relationships between communities, and showcase restoration results to the public. These activities have spurred increased public interest in Mio motorbike restoration and accelerated the spread of this trend from Java to Bali. This research suggests that social media functions not only as a means of communication but also as a catalyst for the formation of hobby-based communities capable of generating economic value through increased demand for spare parts, restoration services, and digital marketing activities.